2020
DOI: 10.1002/jcp.29526
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA expression profiles during the NEL‐like 1 protein–induced osteogenic differentiation

Abstract: Long noncoding RNAs (lncRNAs) are important modulators of mesenchymal stem cells (MSCs) in cellular differentiation. However, the regulatory mechanisms of lncRNAs in NEL-like 1 (NELL-1)-induced osteogenic differentiation of human adipose-derived stem cells remain elusive. Expression profiles of lncRNAs and messenger RNAs during NELL-1induced osteogenesis were obtained using high-throughput sequencing. Gene Ontology, Kyoto Encyclopedia of Genes and Genomes pathway analysis, and gene coexpression networks were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Ubiquitination and degradation of β-catenin are regulated by the balance of GSK-3β and p-GSK-3β [22]. β-Catenin interacts with TCF/LEF-1 or other transcription coactivators in the nucleus and induces the expression of osteogenesis-related molecules to regulate osteogenesis [24,25,47]. Compared with CON-ASCs, DOP-ASCs exhibited relatively downregulated expression of β-catenin, p-GSK-3β, RUNX2, and OPN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ubiquitination and degradation of β-catenin are regulated by the balance of GSK-3β and p-GSK-3β [22]. β-Catenin interacts with TCF/LEF-1 or other transcription coactivators in the nucleus and induces the expression of osteogenesis-related molecules to regulate osteogenesis [24,25,47]. Compared with CON-ASCs, DOP-ASCs exhibited relatively downregulated expression of β-catenin, p-GSK-3β, RUNX2, and OPN.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt signaling pathway is a highly conserved signaling pathway. Abnormal changes in Wnt signaling pathway markers are linked to changes in bone metabolism and the osteogenic ability of mesenchymal stem cells [23][24][25][26]. Recent study has shown that JNK1 is essential for osteoblast function in vivo and in vitro [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that 323 lncRNAs were expressed differentially during osteogenesis and during NELL-1-induced osteogenesis. 114…”
Section: The Role Of Lncrnas In Osteogenesismentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are defined as a set of noncoding RNAs longer than 200bp that have no protein-coding ability. Evidence is rapidly accumulating on the functions of lncRNAs in epigenetic regulation in the differentiation of MSCs and the occurrence of many diseases[ 18 - 21 ]. In this review, we revisit the epigenetic regulatory mechanisms of lncRNAs involved in DNA methylation and histone modifications and summarize the biological functions of lncRNAs in regulation crucial differentiation- and bone disease-related genes by interacting with key epigenetic modifiers.…”
Section: Introductionmentioning
confidence: 99%